Islamofobia Dalam Perkembangan Kajian Teoritis Tafsir Di Indonesia - Setiawan, Priatna Agus (Jurnal Studi Islam, 2025)
This study examines the influence of Islamophobia as a social, political, and intellectual challenge to the development of exegesis studies in Indonesia. In a global context that often marginalizes Islam through negative stigma and stereotypes, Qur’anic exegesis is required to move beyond the normative-traditional approach to an inclusive, dialogical, and contextual one. Through literature review and discourse analysis, this paper explores the role of Indonesian exegetes—such as Quraish Shihab, Sahiron Syamsuddin, and institutions such as the Lajnah Pentashihan Mushaf Al-Qur’an—in repositioning exegesis as a medium for clarification and resistance to the negative image of Islam in the global public sphere. The study’s findings indicate that exegesis has now become a dialectical space between text and context and a means of constructing a peaceful, moderate Islamic narrative that is open to interfaith and intercultural dialogue. This study emphasizes the importance of an adaptive exegesis paradigm in responding to the pressures of systemic Islamophobia. Countermeasure strategies include moderate religious education, an inclusive curriculum, a transformative spiritual approach, and the use of media as a contextual da’wah tool. The synergy between education, media, and public policy strengthens the position of interpretation as a strategic instrument in building a rational and relevant image of Islam in contemporary global dynamics.